Analysis of Effect of Schisandra in the Treatment of Myocardial Infarction Based on Three-Mode Gene Ontology Network - Hu, Siyao; Zuo, Huali; Qi, Jin; Hu, Yuanjia; Yu, Boyang (Frontiers in Pharmacology, 2019)
Schisandra Chinensis is a commonly used traditional Chinese medicine (TCM), has been widely used in the treatment of acute myocardial infarction (AMI) in China. However, the complex mechanism induced by multi-component made it difficult to systematically evaluate the magnitude of the effect of Schisandra in the treatment of AMI. In order to solve this problem, a comprehensive network analysis method was established based-on “component–gene ontology–effect” interactions. Through the network analysis, the suppression of myocardial contractility was identified to be the major effect of Schisandra components, and this network-based identification was further experimentally validated. In addition, the expression of NCOR2 and NFAT in myocyte were experimentally confirmed to be associated with Schisandra in the treatment of AMI, which may be responsible for the pharmacological effects of Schisandra. In conclusion, the three-mode gene ontology network would be an effective network analyze workflow which was feasible for the evaluation of the pharmacological effect of a multi-drug complex system.